2011
DOI: 10.1016/j.procbio.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The first serine protease inhibitor from Lasiodora sp. (Araneae: Theraphosidae) hemocytes

Abstract: This work reports, for the first time, the purification, characterization and antibacterial activity of an elastase inhibitor from Lasiodora sp. hemocytes (EILaH). The hemocyte extract inhibited chymotrypsin (22%), trypsin (44%), tissue plasminogen activator (52%), urokinase (58%) and human neutrophil elastase (99%). EILaH was purified by Trypsin-Sepharose column and RP-HPLC. SDS-PAGE of EILaH revealed a molecular mass of 8 kDa and MALDI-TOF mass spectrometry revealed a single molecular mass of 8274 Da. The am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The P4 fraction contains the protease with greatest proteolytic activity and the highest degree of purification measured in this study, and we suggest that it belongs to the same class of metalloproteases with molecular weight in the range of 40–60 kDa. Proteases are present in the digestive fluids of different species of spiders, just as protease inhibitors have been reported and characterized in several studies [ 56 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The P4 fraction contains the protease with greatest proteolytic activity and the highest degree of purification measured in this study, and we suggest that it belongs to the same class of metalloproteases with molecular weight in the range of 40–60 kDa. Proteases are present in the digestive fluids of different species of spiders, just as protease inhibitors have been reported and characterized in several studies [ 56 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…hemocyte extract against B. subtilis (ATCC-6633), S. aureus (ATCC-6538), E. faecalis (ATCC-6057), E. coli (ATCC-25922) and K. pneumoniae (ATCC-29665) as seen in Table 2. EILaH only showed activity against E. faecalis (MIC = 227.5 µg/mL), while the hemocyte extract presented activity against B. subtilis and E. faecalis (MICs were not present by authors), indicating the presence of other antimicrobial agents in the hemocytes [49].…”
Section: Lasiodora Spmentioning
confidence: 86%
“…Soares et al [49] reported in 2011, the purification and characterization of the first serine protease inhibitor extracted from Lasiodora sp. hemocytes, which was named EILaH.…”
Section: Lasiodora Spmentioning
confidence: 99%
“…The total protein content of hemolymph was represented in mg/mL. The quantification was done using a spectrophotometer at 595 nm (UNICO Spectrophotometer, SP2100 UV, China) [38].…”
Section: Quantification Of Total Hemolymph Proteinsmentioning
confidence: 99%